2016
DOI: 10.1097/scs.0000000000002281
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular Reconstruction in a Patient With Rosai–Dorfman Disease

Abstract: In this rare case, the authors show the difficulties when treating this disease. The follow-up of the patient showed a successful reconstruction with good functional results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…4). Out of the 53 cases studied, 10 displayed unusual symptoms 24,25,33,34,36,43,44,52,53 . Specifically, the symptoms related to the eyes were observed in 5 studies 24,33,34,43,53 , while ear-related symptoms were observed in 3 studies 24,34,36 and paresthesia was seen only in 1 study 44 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Out of the 53 cases studied, 10 displayed unusual symptoms 24,25,33,34,36,43,44,52,53 . Specifically, the symptoms related to the eyes were observed in 5 studies 24,33,34,43,53 , while ear-related symptoms were observed in 3 studies 24,34,36 and paresthesia was seen only in 1 study 44 .…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the immunohistochemical analysis, out of the 29 studies, 5 11,13,36,52,58 showed a positive result for CD1a, while the rest were negative. Cyclin d1 levels were reported in only 2 studies, with Adam et.…”
Section: Resultsmentioning
confidence: 99%